Minutes of 24th technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 24th Technical and Progress Monitoring (TPM) meeting (session II) of BRACU new campus, held on 8th December, 2019.